2015
DOI: 10.1108/ajim-12-2014-0183
|View full text |Cite
|
Sign up to set email alerts
|

Book or NOOK? Information behavior of academic librarians

Abstract: Purpose -The purpose of this paper is to understand patterns in information behavior of academic librarians, individuals who influence information technology adoption in academic libraries and parent institutions. Librarians' perception of their student patrons' information behavior was also investigated. Design/methodology/approach -An exploratory study investigated professional and personal information behavior of eight librarians employed by various academic institutions in the Greater New York City area. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The codified forms of explicit knowledge can be studied as information, and researchers in LIS have long been concerned with information behavior in the workplace (Widén et al, 2014). Yet, while some research has looked into the information behavior of library staff-e.g., their use of technology (Maceli & Burke, 2016) and workplace information literacy (McDonald et al, 2015)-much of this research focuses on how library staff can support the literacy efforts of visitors to the library. Additional research is suggested into how library staff, themselves, create, find, and use explicit knowledge to help them complete work tasks and make sense of their lives at work.…”
Section: What Is Knowledge Work?mentioning
confidence: 99%
“…The codified forms of explicit knowledge can be studied as information, and researchers in LIS have long been concerned with information behavior in the workplace (Widén et al, 2014). Yet, while some research has looked into the information behavior of library staff-e.g., their use of technology (Maceli & Burke, 2016) and workplace information literacy (McDonald et al, 2015)-much of this research focuses on how library staff can support the literacy efforts of visitors to the library. Additional research is suggested into how library staff, themselves, create, find, and use explicit knowledge to help them complete work tasks and make sense of their lives at work.…”
Section: What Is Knowledge Work?mentioning
confidence: 99%
“…Several models and theories have been reported in the literature in the study of the information-seeking behaviour of different categories of people such as farmers (Phiri, 2017), students (Chawinga and Zozie, 2016; Chipeta et al, 2018), and prisoners (Mwuese et al, 2015). The most popular models are Wilson’s 1981 model of information-seeking behaviour (Al-Wreikat et al, 2015); Dervin’s 1983 sense-making theory (Chaudhry and Al-Mahmud, 2015); Ellis’s 1989 and 1993 behavioural model of information-seeking strategies (McDonald et al, 2015; Zhang, 2015); Kuhlthau’s 1991 model of the stages of information-seeking behaviour (Katuu, 2015); and Wilson’s 1996 model of information behaviour (Lavranos et al, 2015; Sahib et al, 2015), which expands his 1981 model through an analysis of the literature in fields other than information science. This study adopted Wilson’s 1996 model of information-seeking behaviour to study the information behaviour of inmates and staff at Mzimba Prison.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Easton, Adam, Durnan, and McLeod () recently investigated user typologies in Scottish NHS libraries, concluding that most users were eNinjas (preference for non‐traditional study and information provided through technology). There is a consensus that users will increasingly play a role in the development of ‘e’ collections and that librarians must ‘stay attuned to their users’ preferences' (McDonald, Risenfiled, Furlow, Kron, & Lopatovska , p. 386). Changing user behaviours such as increased use of personal devices to access eContent will also be influential in future provision (Gilbert & Fister, ).…”
Section: Background and Rationalementioning
confidence: 99%